PERFORMANCE EVALUATION OF HANDOVER TECHNIQUES IN VEHICULAR NETWORKS - Abdullah Alsaadi, Rafid Najm (Journal of mechanics of continua and mathematical sciences, 2024)
The VANET customized vehicle network's versatility, cost-effectiveness, accurate sensing, and potential to open up new and exciting remote sensing applications make it an intriguing subject of study. VANET, short for Vehicular Ad Hoc Network, is a network designed to build an automobile network for a specific purpose. VANETs are being developed as reliable networks used by automobiles to prevent road accidents and ensure passenger safety. They also allow automobiles to communicate, sending emergency alerts and entertainment updates on highways and in cities. VANET is a mobile network that predicts and assists drivers and others in life-threatening and road safety-related circumstances. Despite their many benefits, these networks face many challenges due to their nature. Random movement patterns and high-speed mobility change network structure, resulting in frequent deliveries. This issue is especially important in dedicated vehicle networks, which we will discuss here. This article investigates the possibility of transitioning from VANET to the incorporation of LTE, SDN, and ultimately 5G to establish performance.